Reducing the causal illusion: a question of motivation or of information? - Aranzazu Vinas; Fernando Blanco; Helena Matute (Royal Society Open Science)
The causal illusion is a cognitive bias that involves believing that one event causes another when it does not. It has negative consequences in different spheres of life, including health. Therefore, diverse interventions have been designed to reduce it. The more common ones are educational interventions. These include different elements related to improving both, motivation and information. We wanted to explore which of the two factors was more important for their effectiveness. We first used financial incentives to promote motivation (experiments 1a and 1b), but did not find them effective. Second, we used debiasing instructions about what has to be done to infer the causal relationship between two events accurately. This effectively reduced the causal illusion when the circumstances were in place for the illusion to be high (experiment 2). We discuss the results and their theoretical and practical implications.